2020
DOI: 10.1186/s12967-020-02519-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different omega-3 fatty acid sources on lipid, hormonal, blood glucose, weight gain and histopathological damages profile in PCOS rat model

Abstract: Background Omega-3 fatty acids (Ω-3 PUFAs) may help to improve health status in polycystic ovarian syndrome (PCOS) by reducing numerous metabolic disorders (insulin sensitivity, hyperinsulinemia, lipid profile, obesity and inflammation). To evaluate the current objective, 16 weeks (6 weeks of adjustment period followed by 10 weeks of collection period) research trial was planned to check the impact of different sources of Ω-3 PUFAs (synthetic Ω-3, flaxseed and fish oil) on nutrient digestibility, weight gain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 48 publications
4
29
1
Order By: Relevance
“…Table 3 shows the associations between dietary omega-3 PUFAs and PCOS. For With regard to the long-chain omega-3 PUFAs in serum phospholipids, both the medians of total and long-chain omega-3 PUFAs were significantly lower in the cases than in the controls ( 4 10.99] for long-chain omega-3 PUFAs; both p < 0.001). Consistently, the median values of all serum phospholipid omega-3 PUFA levels were significantly lower in the cases than in the controls (all p < 0.001) (Table 2).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Table 3 shows the associations between dietary omega-3 PUFAs and PCOS. For With regard to the long-chain omega-3 PUFAs in serum phospholipids, both the medians of total and long-chain omega-3 PUFAs were significantly lower in the cases than in the controls ( 4 10.99] for long-chain omega-3 PUFAs; both p < 0.001). Consistently, the median values of all serum phospholipid omega-3 PUFA levels were significantly lower in the cases than in the controls (all p < 0.001) (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have demonstrated that a specific diet containing n-3 PUFA, especially long-chain PUFA, significantly improved the clinical manifestations of dyslipidaemia, vascular endothelial dysfunction and insulin resistance in patients with PCOS (8,9) . Komal et al (10) reported that fish oil, as a source of EPA and DHA, reduced body weight and metabolic anomalies in an animal model. One meta-analysis involving 591 PCOS patients from nine randomised controlled trials indicated that supplementation with n-3 PUFA may improve the insulin resistance index and adiponectin level as well as decrease total cholesterol and total TGA levels (9) .…”
mentioning
confidence: 99%
“…The study focused on differences in FA profiles of abdominal subcutaneous adipose tissue between pregnant women with and without PCOS found that total PUFA was lower in PCOS than non-PCOS women ( p < 0.004) [ 22 ]. The animal model study also showed that ω-3 PUFA had an effective role in improving lipid and hormonal profile, reducing blood glucose, body weight and histopathological damages in PCOS rats [ 23 ]. Based on the positive role of FAs in normal lipid metabolism and ovarian function in PCOS, therefore, in this study, the significantly changed FAs were all down-regulated in PCOS patients, which were coincident with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In the ovary, the presence of cystic follicles with a thin layer of granulosa cells and the absence of corpus luteum (indicative of anovulation status) is a common finding. 6 One of the most basic treatment lines of PCOS is metformin. Metformin is a biguanide used to treat hyperglycemia, reduce insulin resistance, and inhibit hepatic gluconeogenesis.…”
Section: Ethical Publication Statementmentioning
confidence: 99%